Peningkatan Kompetensi UMKM dalam Penyusunan Anggaran Penjualan di Cikarang Pusat - Asiah, Neng; Yahya, Adibah; Asti, Eka Geovana; Permana, Indra; Hidayat, Nazwa Putri; Muarif, Dede Samsul (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The goal of sales budget support is to help companies or organisations create, implement, and oversee their own sales budget. The amount left over from the purchase price after products or services are sold for a predetermined period of time is known as the selling price. Analysing past data, answering client questions, determining target markets, and creating winning marketing campaigns are all steps in the process of creating a sales budget. The purpose of this step is to assist employees of SMEs in lowering sales pressure in the context of money management and business growth. This activity is intended to disseminate information about the advantages of lowering the purchase price, how fair competition can assist SMEs in reaching their financial objectives, and how this process can be maximised. This activity is anticipated to offer insights into the advantages of sales budget support, how SMEs may attain their financial objectives with the appropriate strategy, and how this process can be improved for increased efficacy. By offering advice on how businesses should plan and manage their sales budgets, this activity can also add to the body of knowledge on financial management and business planning. Over time, support from sales budgets can play a significant role in a company's ability to succeed and expand sustainably.